2015
DOI: 10.3899/jrheum.141067
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and Reproducibility of Ultrasonography in Calcium Pyrophosphate Crystal Deposition in Knee Cartilage: A Cross-sectional Study

Abstract: US of knees is more sensitive than radiography for CPPD diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
2
14
1
Order By: Relevance
“…In addition to the subgroups described above, we also compared the test characteristics of US in patients with MSU-positive gout with the subgroup of controls with CPDD. CPDD is associated with similar US findings (12,13,(16)(17)(18)(19). In our study, the specificity of US for gout remained .80%.…”
Section: Discussionsupporting
confidence: 80%
“…In addition to the subgroups described above, we also compared the test characteristics of US in patients with MSU-positive gout with the subgroup of controls with CPDD. CPDD is associated with similar US findings (12,13,(16)(17)(18)(19). In our study, the specificity of US for gout remained .80%.…”
Section: Discussionsupporting
confidence: 80%
“…In the present study, US findings indicative of CPP crystal deposits were more frequently detected at the acetabular labrum fibrocartilage than at the femoral head's hyaline cartilage. This result is consistent with what had been shown at knee level in previous US studies where CPP crystal deposits were more frequently found at the meniscal fibrocartilage than at the femoral condyles' hyaline cartilage, with the exception of 1 study in which US calcifications were more frequently detected at the femoral condyles' hyaline cartilage than at the meniscal fibrocartilage .…”
Section: Discussionsupporting
confidence: 92%
“…The opportunity to consider the hip as a sentinel region for the detection of CPP crystal deposits even in the absence of knee involvement is clinically relevant, especially in patients with joint pain of unknown origin. US has gained a well‐defined role in the diagnosis of CPPD, having shown a greater or equal sensitivity and comparable specificity to CR in the detection of CPP crystal aggregates . However, to the best of our knowledge, there is no study that has compared the diagnostic accuracy of US and CR in the evaluation of CPP crystal deposits at the hip joint in patients with CPPD.…”
Section: Introductionmentioning
confidence: 99%
“…CPPD deposits were slightly more common in our cohort (37.5% in HH-WA and 61.5% in HH-A) than in previous cohorts of patients with HH (30–50%) [ 7 ]. We explain this by the greater sensitivity of ultrasound to detect CPPD as compared to other methods such as radiography or synovial fluid aspiration [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%